2000
DOI: 10.1128/jb.182.24.6913-6920.2000
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Horizontal Gene Transfer in Evolution of Elongation Factor Tu in Enterococci

Abstract: The elongation factor Tu, encoded by tuf genes, is a GTP binding protein that plays a central role in protein synthesis. One to three tuf genes per genome are present, depending on the bacterial species. Most low-G؉C-content gram-positive bacteria carry only one tuf gene. We have designed degenerate PCR primers derived from consensus sequences of the tuf gene to amplify partial tuf sequences from 17 enterococcal species and other phylogenetically related species. The amplified DNA fragments were sequenced eith… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(45 citation statements)
references
References 48 publications
2
42
1
Order By: Relevance
“…35 The tuf gene was used because it is better at differentiating different species of staphylococci and other Gram-positive bacteria. 36 The results of this study confirmed our previous results 11 that pretreatment of viable bacterial cells with PMA is associated with a small difference in the C t -the cycle at which the amplified product become ''positive'' in a real-time PCR assay-whereas dead cells are associated with a large C t difference. Antibiotic killing with gentamicin resulted in a smaller effect of PMA treatment on subsequent PCR than did heat-inactivation and vancomycin in both strains.…”
Section: Discussionsupporting
confidence: 89%
“…35 The tuf gene was used because it is better at differentiating different species of staphylococci and other Gram-positive bacteria. 36 The results of this study confirmed our previous results 11 that pretreatment of viable bacterial cells with PMA is associated with a small difference in the C t -the cycle at which the amplified product become ''positive'' in a real-time PCR assay-whereas dead cells are associated with a large C t difference. Antibiotic killing with gentamicin resulted in a smaller effect of PMA treatment on subsequent PCR than did heat-inactivation and vancomycin in both strains.…”
Section: Discussionsupporting
confidence: 89%
“…This should not decrease the accuracy of the analysis since the differences in the tree topology were observed in more than one species of the same genus (e.g., Streptococcus). The genome sequence analysis showed that horizontal gene transfer is an event that also occurs frequently in housekeeping genes, like the tuf gene (16), and in the S14 gene encoding the ribosomal protein (5).…”
Section: Discussionmentioning
confidence: 99%
“…tution of Thr-230 with Ser in the third ␤ strand of the second domain of the protein, which comprises the aminoacyl-tRNA binding pocket (25). The effects of pneumococcal EF-Tu addition on the generation of misaminoacylated tRNA Ala and tRNA Phe by AlaRS were investigated.…”
Section: Journal Of Biological Chemistry 25919mentioning
confidence: 99%